GREEN BANKING AS A MONEY LAUNDERING PREVENTION INSTRUMENT: IMPLICATIONS FOR THE FINANCIAL SECTOR AND THE ENVIRONMENT - Hamdani Maakir; Joko Susetyanto, Zico Junius Fernando (Adisam Publisher, 2024)
Indonesia's financial sector is undergoing a transformative shift through the integration of green banking principles, marking a significant stride towards sustainable development and the bolstering of financial integrity. This paper explores the proactive measures taken by Indonesia, including the adoption and adaptation of international initiatives such as the Global Alliance for Banking on Values, Green Development Banks, the Network for Greening the Financial System (NGFS), the utilization of blockchain technology, and the implementation of Environmental, Social, and Governance (ESG) standards. These steps not only align with the global Sustainable Development Goals (SDGs) but are also tailored to meet Indonesia's unique environmental, socio-economic challenges. The commitment of Bank Indonesia and the Financial Services Authority (OJK) to mandate and nurture green banking practices is a testament to the country's dedication to a sustainable future, simultaneously enhancing the financial sector's resilience against crimes like money laundering. The emphasis on transparency and accountability through mandated sustainability reporting emerges as a key strategy in establishing trust and credibility amongst stakeholders. However, challenges in the consistent implementation of green banking practices and sustainability reporting underscore the need for clear, measurable standards and comprehensive education and training. The convergence of environmental sustainability with anti-money laundering efforts epitomizes a synergistic approach to strengthening the financial sector's stability and transparency. This paper concludes that green banking in Indonesia transcends regulatory compliance, embodying a strategic imperative that leverages environmental stewardship as a foundation for secure, transparent, and ethical banking. Indonesia's evolving green banking framework not only contributes to global sustainability efforts but also sets a benchmark for integrating economic growth with environmental conservation, paving the way for a sustainable and prosperous future. This study illuminates Indonesia's role as a pioneer in the fusion of sustainability and financial integrity within the banking sector.